THE IMPACT OF COMMUNITY HEALTH EDUCATION ABOUT STUNTING ON MOTHERS’ KNOWLEDGE LEVELS - Alicia Nayoan; Beverlee Kawalo; Gabriella Tulungen; Sultan Gultom; Carlos Sagala; Lyna Hutapea (Jurnal Cakrawala Ilmiah, 2023)
Stunting has become a concern that attracts the attention of health leaders worldwide. Stunting is defined as a condition wherein a child experiences chronic inadequacy of nutrition consumption that leads them to growing slower than the others their age, manifested clearly in their height. Stunting leads to a lot of disadvantages not only for the child, but also to the family, and even further to the country’s future economy. Indonesia has been found to have a number of stunting prevalence higher than what has been determined by the World Health Organization. Mothers play a great role in preventing stunting from spreading even further. The aim of this study is focused on measuring the knowledge of the mothers with toddlers about stunting and how a community health education done regarding the topic concerned can influence their fore knowledge. This study is done in the design of quantitative method, using the pretest-posttest control group design. The health education is given to mothers with toddlers living in a village named Karyawangi in West Bandung, Indonesia. The result shows that there is a positive impact found towards the knowledge of the participants before and after the health education is given. The scoring of the pre- and post- test shows a positive difference, leading to a higher value. It is then recommended that health education on stunting needs to be done more frequently to raise the awareness of mothers in regards of reducing the number of children with stunting.